2014
DOI: 10.1371/journal.pone.0096022
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Traits but Not Diversity Mitigate Stem Breakage in a Subtropical Forest following a Rare and Extreme Ice Storm

Abstract: Future climates are likely to include extreme events, which in turn have great impacts on ecological systems. In this study, we investigated possible effects that could mitigate stem breakage caused by a rare and extreme ice storm in a Chinese subtropical forest across a gradient of forest diversity. We used Bayesian modeling to correct stem breakage for tree size and variance components analysis to quantify the influence of taxon, leaf and wood functional traits, and stand level properties on the probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…2011b), and maintained high leaf photosynthetic capacity concurrently with low freezing resistance, suffered more physical and physiological damage from the ice storm than the deciduous (Nadrowski et al. 2014; Rehm et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011b), and maintained high leaf photosynthetic capacity concurrently with low freezing resistance, suffered more physical and physiological damage from the ice storm than the deciduous (Nadrowski et al. 2014; Rehm et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2011b; Nadrowski et al. 2014). Furthermore, ice storm-damaged canopies induced low recruitment of some species via reduced flowering opportunities, seed production (Du et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tree size was an important factor in determining its susceptibility to ice damage (Rhoads et al 2002, Wang et al 2009, Su et al 2010, Man et al 2011, Nadrowski et al 2014. Many studies reported that larger trees received more damage from ice storms (Platt et al 2000, Nielsen et al 2003, Su et al 2010, Man et al 2011.…”
Section: Factors Affecting Ice Damage Severitymentioning
confidence: 99%
“…Partly because of this, ice storms and their associated risks are rarely considered in ecosystem management (Zhou et al 2011b). Ice damage to trees is likely to depend on tree size, crown form, wood mechanical properties, stand structure, and many other factors in addition to ice storm intensity (Nadrowski et al 2014). Since ice storms do not occur frequently in subtropical regions, research does not usually address ice damage to subtropical forests, where biodiversity is higher and the ecosystem structure is more complex than temperate forests (Bragg et al 2003, Nadrowski et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation